1993
DOI: 10.1200/jco.1993.11.10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and pharmacologic study of paclitaxel and cisplatin with granulocyte colony-stimulating factor: neuromuscular toxicity is dose-limiting.

Abstract: Taxol and cisplatin doses of 250 mg/m2 and 75 mg/m2, respectively, can be administered repetitively with G-CSF to untreated and minimally pretreated patients. However, these doses are not recommended for patients with pre-existing neuropathies until additional experience in high-risk patients is obtained. Although this Taxol dose is nearly 85% higher than the dose that can be combined with cisplatin in the absence of G-CSF, this high-dose regimen should not be used outside the investigational setting until a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
60
1
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(65 citation statements)
references
References 10 publications
3
60
1
1
Order By: Relevance
“…Neuropathy has also been reported as a dose-dependent side-effect of treatment with paclitaxel (Taxol) (Lipton et al, 1989;Gerven et al, 1994). As expected, trials on combination chemotherapy of cisplatin and paclitaxel found a high incidence of peripheral neuropathy (Rowinsky et al, 1991;Rowinsky et al, 1993;Chaudhry et al, 1994).…”
supporting
confidence: 75%
See 3 more Smart Citations
“…Neuropathy has also been reported as a dose-dependent side-effect of treatment with paclitaxel (Taxol) (Lipton et al, 1989;Gerven et al, 1994). As expected, trials on combination chemotherapy of cisplatin and paclitaxel found a high incidence of peripheral neuropathy (Rowinsky et al, 1991;Rowinsky et al, 1993;Chaudhry et al, 1994).…”
supporting
confidence: 75%
“…Neuropathy has also been reported as a dose-dependent side-effect of treatment with paclitaxel (Taxol) (Lipton et al, 1989;Gerven et al, 1994). As expected, trials on combination chemotherapy of cisplatin and paclitaxel found a high incidence of peripheral neuropathy (Rowinsky et al, 1991;Rowinsky et al, 1993;Chaudhry et al, 1994).Peripheral neurotoxicity has been reported as a frequent, but usually mild side-effect of docetaxel in several phase I and phase II studies (Bissett et al, 1993;Extra et al, 1993;Aamdal et al, 1994;Fossella et al, 1994;Francis et al, 1994a;Francis et al, 1994b;Smyth et al, 1994;Chevallier et al, 1995; Hilkens et al, 1996;New et al, 1996). The neurotoxic effects of docetaxel in combination Chemotherapy was administered in 3-weekly regimens.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…The risk of neutropenia has been significantly reduced in recent years by using shorter infusion times and the administration of granulocyte colony stimulating factors. 4,5 On the other hand, neurotoxicity cannot be prevented nor treated, can last for months, and in severe cases it may cause irreversible nerve damage. 6,7 Neurotoxicity, which has become the dose-limiting toxicity of paclitaxel, exhibits substantial interindividual variability.…”
Section: Introductionmentioning
confidence: 99%